ALGORITHMIC JUDGEMENT VERSUS PROFESSIONAL SKEPTICISM: REDEFINING AUDITOR DECISION-MAKING IN AI-SUPPORTED AUDITS - Jefry Gasperz; Margaretha Titaley; Rasyid Latuconsina (Adisam Publisher, 2026)
The development of artificial intelligence technology has brought significant changes to audit practice, particularly through the use of AI systems to support auditor decision-making. The emergence of intelligent algorithms has sparked debate regarding the role of algorithmic judgment versus auditor professional skepticism in the audit process. This study aims to analyze and redefine the dynamics of auditor decision-making in the context of AI-based audits using a literature review method. The literature review was conducted by reviewing various academic publications, professional reports, and empirical research related to the implementation of AI in audits, its impact on professional judgment, and the challenges in maintaining professional skepticism. The results indicate that although AI algorithms improve the efficiency and accuracy of risk detection, there is a risk of overreliance, which can reduce the level of auditor skepticism. This study emphasizes the importance of integrating professional judgment and critical evaluation of AI output, so that auditors maintain their oversight and independent assessment. These findings provide a theoretical contribution to the development of a modern audit framework that combines AI capabilities with the principle of professional skepticism.